Analisis Faktor-Faktor yang Mempengaruhi Siswa SMU di Tangerang dalam Keputusan Pembelian Kartu IM3 Prabayar - Anindita, Rina (Jurnal Ekonomi : Journal of Economic, 2010)
This study aimed to determine the factors that affect its students any high school in Tangerang to buy prepaid cards IM3. In this study the factors that influence purchasing decisions in terms of marketing mix (4P). The results of this study indicate that there are factors that influence consumers in their buying decision IM3 prepaid card. These factors enter into 9 new factors are: Factor 1 has the name of Excellence which consists of a broad scope of IM3, Bonus sms, Nominal pulse varied, sophisticated multimedia, fast data transfer, and 3G technology, GPRS, MMS provided, factor 2 was named Privileges consisting of an sms package voucher price they can afford, talk per second rate, and ease of getting a voucher, Factor 3 was named facility consisting of card availability IM3, IM3 voucher availability, and ads on television, Factor 4 Ease named consisting of GPRS settings, MMS, and 3G is easy, efficient tariff until satisfied, and IM3 Ce eS's, factor 5, was named Promotion consisting of the radio ads, brochures, pamphlets, posters, Event, held IM3 , and send 10 free 10 sms, Factor 6 was named design consisting of an interesting shape or packaging, design an attractive card, and design an attractive voucher, factor 7 was named Quality of service consisting of a satisfactory service, after-sales service / warranty , and the quality is strong and stable network, Factor 8 was given a name consisting of Availability Availability Gallery Indosat, and Factor 9 was named The price of a cheap price sms vouchers, and vouchers to speak at affordable prices.Â Keywords: Factors that Influence Consumers, Marketing Mix, Purchasing Decisions